MECHANISM FOR MANAGING HUMAN RESOURCES IN HEALTHCARE INSTITUTIONS - Margasova, Viktoriia; Husarevych Natalіia (Current Problems of Sustainable Development, 2026)
The healthcare system of Ukraine operates in conditions of martial law, socio-economic instability and demographic transformations. Under such conditions, the issue of forming and effective use of the human resources potential of healthcare institutions becomes particularly relevant. The reduction in the number of medical workers, the increasing staff shortage, migration processes and the increasing workload on personnel necessitate the improvement of approaches to human resources management in the medical sector. This determines the need to develop a mechanism for managing human resources potential that can ensure the sustainable development of healthcare institutions and improve the quality of medical services. The purpose of the study is to study the theoretical principles of managing the human resources potential of healthcare institutions, assess current trends in its development and substantiate the directions for strengthening the system of human resources provision of healthcare institutions in conditions of socioeconomic volatility and military-political challenges. Materials and methods. The materials of the study are regulatory legal acts of Ukraine and international documents, statistical and analytical data of the State Statistics Service of Ukraine, the Ministry of Health of Ukraine, the National Health Service of Ukraine and the Center for Public Health of the Ministry of Health of Ukraine, scientific works of domestic and foreign researchers on the management of human resources and the development of human capital in the healthcare system. The following scientific methods were used in the research process: theoretical generalization and grouping; system analysis; statistical analysis; system-structural approach; logical generalization of results. Results. The article examines modern trends in the development of human resources in healthcare institutions in Ukraine. It has been established that there is a steady trend towards a reduction in the number of doctors, which indicates an increase in the personnel shortage in the industry. It is substantiated that the effectiveness of staffing depends on the level of professional competencies of personnel, the motivation system, digital literacy and the ability of employees to adapt to modern challenges. A mechanism for managing the human resources of healthcare institutions has been developed, which is based on the interaction of organizational, motivational, developmental and innovative-digital management areas. The proposed mechanism takes into account the influence of external and internal factors on the functioning of medical institutions and is aimed at the development, preservation and effective use of human resources. The practical value of the developed mechanism lies in the creation of a comprehensive human resources management system that contributes to improving the quality of medical services, the efficiency of human capital use and ensuring the sustainable development of healthcare institutions. Discussion. Prospects for further scientific research include the development of methodological approaches to assessing the effectiveness of personnel investments, determining indicators of the effectiveness of human resources management and the formation of tools for monitoring the personnel security of healthcare institutions in the context of digital transformation and post-war recovery.